Alkaline surface modification engineering of MXene ultrathin nanosheet and application of MXene ultrathin nanosheet in ion capture
By intercalating and modifying MXene with alkali, the problems of MXene self-stacking and oxidation were solved, the electrochemical performance and ion adsorption capacity were improved, and its application in energy storage and electrochemical catalysis was expanded.
Patent Information
- Application Number
- CN202511229266.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-12
AI Technical Summary
Existing MXene materials suffer from self-stacking due to van der Waals forces, resulting in reduced exposure of electrochemical active sites and slow ion transport rates. Additionally, surface metal atoms are easily oxidized, limiting their electrochemical performance and lifespan.
By intercalation modification through alkali treatment, the interlayer spacing and surface electron cloud density of MXene are adjusted to form an electron-rich material, which enhances electrostatic attraction and promotes ion adsorption.
It significantly improves the electrochemical performance of MXene, enhancing its specific capacity and ion adsorption properties. It is suitable for applications such as supercapacitors, batteries, and catalysts, and features high efficiency, stability, and low cost.
Smart Images

Figure CN121107413A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a kind of modification MXene by alkali treatment, form surface electron-rich material, especially applied to ion adsorption.The technology belongs to electrochemical catalyst and energy storage field, specifically for the capture of a variety of ions. BACKGROUND
[0002] With the continuous growth of global population and the intensification of industrial wastewater pollution, water resource shortage is becoming increasingly serious. Of the water resources on earth, about 97% is seawater, only 3% is fresh water, and part of the fresh water cannot be directly used due to geographical or other reasons. Therefore, it is necessary to develop efficient water treatment technology to ensure the stable supply of clean water. Among many water treatment technologies, capacitive deionization technology is considered one of the most promising solutions. Capacitive deionization (CDI) technology has the advantages of low operating voltage (<2V), low energy consumption (0.2-2.03 kWh / m³), renewable and little environmental pollution, and has become an effective technology widely used in brackish water, water softening and wastewater recovery.
[0003] In recent years, a new type of two-dimensional (2D) layered material-MXene has attracted much attention due to its high theoretical capacity, excellent electrical conductivity, good hydrophilicity and excellent intercalation pseudocapacitance. However, due to the action of van der Waals force, adjacent MXene sheets are prone to re-stacking, resulting in reduced exposure of electrochemically active sites and slow ion transport rate. In addition, the surface metal atoms of MXene are easily oxidized, limiting its performance and service life in electrochemistry.
[0004] To overcome these problems, MXene is subjected to alkali intercalation treatment to expand its interlayer spacing and increase the electrochemically active sites. In addition, the electron cloud density of the surface atoms of MXene treated by alkali increases, enhancing the surface negative charge and thus promoting the adsorption of ions through electrostatic attraction.
[0005] The present application successfully solves the problem of easy self-stacking of MXene by precisely adjusting its interlayer spacing and surface functional groups, providing a highly efficient, stable and low-cost material. This technical solution not only provides a new idea for the design of high-efficiency ion capture materials, but also lays a foundation for the development of next-generation clean energy technology. SUMMARY
[0006] The present application relates to a kind of preparation method of alkali treatment intercalation modified material based on MXene, it is intended to realize the regulation and control of material interlayer spacing and the optimization of surface electron cloud density by gradient adjustment alkali solution concentration, to further synergistically improve the electrochemical performance of the material in energy storage device and ion adsorption capacity in environmental governance.The method of the present application includes ultrasonic dispersion treatment to MXene nanosheet to form homogeneous colloidal solution, then under the condition of continuous stirring, introduce alkaline solution, realize the substitution of material surface functional group by room temperature stirring reaction, and effectively improve electron cloud density.The method is simple in operation, strong in adaptability, and can optimize the performance of MXene without changing its basic structure.
[0007] By the preparation method of the present application, the obtained alkali treatment modified MXene shows excellent and significantly improved electrochemical performance, such as high specific capacity, excellent electrical conductivity, higher ion adsorption performance, etc., and is particularly suitable for supercapacitors, batteries, catalysts and other fields.
[0008] The technical scheme of the present application is as follows: a preparation method of alkali treatment surface modified MXene material, the material is prepared from alkali intercalation layered MXene.
[0009] The method for preparing the material includes the following steps: (1) slowly add Ti3AlC2 powder into polytetrafluoroethylene containing concentrated HCl and LiF to etch the aluminum layer, and after etching is completed, wash to neutral; (2) disperse the product obtained in step (1) in water, continuously introduce inert gas for degassing treatment, seal at room temperature for ultrasonic peeling, centrifuge the obtained dispersion, freeze-dry the supernatant to obtain few-layer Ti3C2T x nanosheet; (3) weigh few-layer Ti3C2T x nanosheet, slowly add alkali solution under stirring, stir under inert gas, vacuum suction filter the sample after reaction, wash the filter cake with water until the filtrate is neutral, and freeze-dry to obtain surface functionalized MXene.
[0010] In step (1), the mass ratio of Ti3AlC2 to LiF is 1:1-2, and the mass concentration of concentrated HCl is 36-38%.
[0011] In step (1), the aluminum layer etching temperature is 40-70 ℃, and the etching time is 24-72 h.
[0012] In step (2), the concentration of Ti3C2T x dispersion is 8-12 mg mL -1 .
[0013] In step (2), the inert atmosphere is selected from either nitrogen or argon, the ultrasonic stripping time is 8-15 h, and the centrifugation speed is 3000-5000 rpm. -1 .
[0014] The base in step (3) is selected from any one or more combinations of 2,2'-bipyridine, 2,3'-bipyridine, 2,4'-bipyridine, 4,4'-bipyridine, acridine or phenanthridine.
[0015] The concentration of the alkali is 1-5 M, and the Ti3C2T x The dispersion concentration in alkaline solutions is 0.5-2 mg / mL. -1 .
[0016] In step (3), after adding the alkaline solution, the reaction is carried out for 20-30 hours under the inert gas of argon and nitrogen, with the stirring speed controlled at 800-900 rpm.
[0017] The freeze-drying time in step (2) is 5-7 days.
[0018] Another technical solution of this invention is the application of an alkali-treated surface-modified MXene-based functionalized material in electrochemical ion capture. The electron-rich MXene material obtained through alkali-treated intercalation modification serves as an electrochemically active electrode, utilizing its reconstructed surface charge distribution and expanded interlayer transport channels to achieve the capture of various ions. After basic characterization, the functionalized MXene is subjected to electrochemical testing, the specific methods of which are as follows: Alkali-treated MXene was prepared into a uniform electrode dispersion and drop-coated onto carbon cloth. After drying, the working electrode was successfully obtained with a loading of 2 mg cm⁻¹. -1 The reference electrode is an Ag / AgCl electrode, the counter electrode is a platinum sheet, and the electrolytes are 1 M NaNO3, 1 M Pb(NO3)2, 1 M Al(NO3)3, etc. MXene exhibits excellent electrochemical performance and ultra-long stability when treated with alkali in various ions.
[0019] The beneficial effects of this invention are as follows: (1) The synthesis method is simple and efficient: This invention adopts an alkaline intercalation strategy, and successfully realizes intercalated MXene functionalized materials through liquid phase etching and subsequent intercalation reaction. The synthesis process is simple to operate, has low equipment requirements, and is suitable for large-scale production.
[0020] (2) Optimized structural design: Alkali intercalation significantly extends the structure of Ti3C2T xThe interlayer spacing is reduced, forming a loose, sheet-like structure. Based on the change in alkali concentration gradient, the optimal alkali concentration (3 M) for intercalation was found. At this concentration, the interlayer spacing was optimally matched, providing more active sites for electrochemical reactions and enhancing the contact efficiency with the electrolyte.
[0021] (3) Improved electronic structure and conductivity: The intercalation structure optimizes the electronic structure of the material, increases the electron cloud density on the MXene surface, and significantly reduces the charge transfer resistance, thereby improving the charge transport rate and providing kinetic advantages for ion capture.
[0022] (4) Excellent electrochemical performance: Thanks to the structural optimization and electronic regulation of intercalation, when the base concentration is 3 M, Ti3C2T x In 1 A g -1 Its specific capacitance is higher than that of the original Ti3C2T in various nitrate electrolytes. x Ti3C2T treated with 1 / 5 M alkali x .
[0023] (4) Excellent long-term stability: at 5 A g -1 Stability tests were conducted at current densities of 4000 cycles in +1, +2, and +3 valent ions. The alkali-treated MXene still maintained good structural stability and electrochemical performance.
[0024] (5) Wide range of application potential: The alkaline intercalation modification strategy of the present invention is applicable to the performance optimization of other MXene materials. It not only exhibits excellent performance in ion adsorption, but can also be widely applied in other electrochemical reactions, supercapacitors and other energy storage fields, showing high application prospects and economic value, and has broad market potential. Attached Figure Description
[0025] Figure 1 Ti3C2T synthesized in Example 1 x XRD patterns of intercalated MXene with different alkali concentrations: A represents MXene surface-modified with 5 M alkali, B represents MXene surface-modified with 3 M alkali, and C represents MXene surface-modified with 1 M alkali.
[0026] Figure 2 This is a transmission electron microscope (TEM) image of the intercalated MXene synthesized in Example 1.
[0027] Figure 3 The graph shows the specific capacitance performance of the synthesized sample in Example 1 on 1 M Al(NO3)3 electrolyte.
[0028] Figure 4The graph shows the change in conductivity over time of the synthesized samples from Examples 1, 2, 3, and 4 in a low-concentration Al(NO3)3 electrolyte. A represents MXene surface-modified with 5 M alkali, B represents MXene surface-modified with 3 M alkali, and C represents MXene surface-modified with 1 M alkali. Detailed Implementation Plan The present invention will be further illustrated below with reference to the embodiments, but the scope of protection of the present invention is not limited to the scope described in the embodiments.
[0029] Example 1 A method for preparing the material, the method comprising the following steps: 1) Slowly add 2 g of Ti3AlC2 powder to polytetrafluoroethylene containing 50 mL of concentrated HCl (37%) and 2.2 g of LiF and react for 30 min. Then, stir at 50 °C for 48 h to etch the aluminum layer. After etching, wash the mixture several times with deionized water until the pH value reaches above 6.
[0030] 2) Disperse the product obtained in step (1) in a glass bottle containing deionized water and continuously pass inert gas for degassing. Seal the bottle and ultrasonically peel it at room temperature for several hours. Then, centrifuge the resulting dispersion at a certain speed for 1 hour.
[0031] 3) The supernatant obtained above was freeze-dried to obtain a few-layer Ti3C2T x Nanosheets.
[0032] 4) 150 mg of few-layer Ti3C2T x The MXene was dispersed in 100 mL of 3 M bipyridine solution (added while stirring), and an inert protective gas argon was continuously purged for 30 minutes. The glass bottle was then sealed, and the mixture was stirred at 900 rpm for 24 h at room temperature to obtain alkali-treated surface-modified MXene. The reacted sample was vacuum filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH≈7). Finally, the obtained sample was freeze-dried to obtain 3 M alkali-treated surface-modified MXene with surface functionalization.
[0033] After basic characterization, the 3M alkali-treated surface-modified MXene was subjected to electrochemical testing, the specific methods of which are as follows: A uniform electrode dispersion of surface-modified MXene treated with 3 M alkali was prepared and drop-coated onto carbon cloth. After drying, the working electrode was successfully obtained with a loading of 2 mg cm⁻¹. -1 The reference electrode is an Ag / AgCl electrode, the counter electrode is a platinum sheet, and the electrolyte is a 1 M Al(NO3)3, 1 Ag... -1The specific capacitance at current density is 170 Fg -1 (The detection conditions in other embodiments are the same as in Embodiment 1).
[0034] X-ray diffraction (XRD) analysis showed that the interlayer spacing of MXene increased with increasing alkali concentration gradient, reaching an optimal ion storage space at a concentration of 3 M. Transmission electron microscopy (TEM) analysis indicated that the 3 M alkali-treated surface-modified MXene maintained its ultrathin nanosheet morphology. Furthermore, compared to unmodified Ti3C2T... x In contrast, the surface of these nanosheets showed no changes, indicating that the alkali-treated surface-modified MXene did not exhibit significant oxidation. From... Figure 3 The performance comparison chart shows that alkali treatment significantly improves the performance of MXene, with the best performance observed at an alkali concentration of 3 M. Furthermore, the conductivity decrease was greatest at an alkali concentration of 3 M in the two-electrode test. Figure 3 This demonstrates that 3 M alkali treatment of the surface-modified MXene is most conducive to ion adsorption.
[0035] Example 2 Steps 1-3 are the same as in Example 1.
[0036] 150 mg of few-layer Ti3C2T x Dispersed in 100 mL of 1 M 2,2'-bipyridine solution (added while stirring), the sample was continuously purged with an inert protective gas, argon, for 30 minutes. The glass bottle was sealed, and the mixture was stirred at 900 rpm for 24 h at room temperature to obtain the intercalated sample, 1 M alkali-treated surface-modified MXene. The reacted sample was vacuum filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH≈7). Finally, the obtained sample was freeze-dried to obtain the surface-functionalized MXene. 1 M alkali-treated surface-modified MXene was then dissolved in 1 M Al(NO3)3 solution with 1 Ag... -1 The specific capacitance at current density is 125 F.g -1 .
[0037] Example 3 Steps 1-3 are the same as in Example 1.
[0038] 150 mg of few-layer Ti3C2T xDispersed in 100 mL of 5 M bipyridine solution (added while stirring), the sample was continuously purged with an inert protective gas, argon, for 30 minutes. The glass bottle was sealed, and the mixture was stirred at 900 rpm for 24 h at room temperature to obtain the intercalated sample, 5 M alkali-treated surface-modified MXene. The reacted sample was vacuum filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH≈7). Finally, the obtained sample was freeze-dried to obtain the surface-functionalized MXene. 5 M alkali-treated surface-modified MXene was then dissolved in 1 M Al(NO3)3 solution with 1 Ag... -1 The specific capacitance at current density is 110 F.g -1 .
[0039] Example 4 (Ti3C2T) x (Preparation) 2 g of Ti3AlC2 powder was slowly added to a mixture of 50 mL concentrated HCl (37%) and 2.2 g LiF in polytetrafluoroethylene and reacted for 30 min. The mixture was then stirred at 50 °C for 48 h to etch the aluminum layer. After etching, the mixture was washed repeatedly with deionized water until the pH reached above 6. The product obtained was dispersed in a glass bottle containing deionized water, and degassed continuously with inert gas. The bottle was then sealed and ultrasonically peeled at room temperature for several hours. The resulting dispersion was then centrifuged at a certain speed for 1 hour to obtain a few-layer Ti3C2T. x Ti3C2T x 1 Ag in 1 M Al(NO3)3 solution -1 The specific capacitance at current density is 97 Fg -1 .
[0040] Example 5 Steps 1-3 are the same as in Example 1.
[0041] 150 mg of few-layer Ti3C2T x Dispersed in 100 mL of 3 M 4,4'-bipyridine solution (added while stirring), the sample was continuously purged with an inert protective gas, argon, for 30 minutes. The glass bottle was sealed, and the mixture was stirred at 900 rpm for 24 h at room temperature to obtain the intercalated sample, 3 M alkali-treated surface-modified MXene. The reacted sample was vacuum filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH≈7). Finally, the obtained sample was freeze-dried to obtain the surface-functionalized MXene. 3 M alkali-treated surface-modified MXene was then dissolved in 1 M Al(NO3)3 solution with 1 Ag... -1 The specific capacitance at current density is 165 Fg -1 .
[0042] Example 6 Steps 1-3 are the same as in Example 1.
[0043] 150 mg of few-layer Ti3C2T x Dispersed in 100 mL of 3 M acridine solution (added while stirring), the sample was continuously purged with argon gas for 30 minutes. The glass bottle was sealed, and the mixture was stirred at 900 rpm for 24 h at room temperature to obtain the intercalated sample, 3 M alkali-treated surface-modified MXene. The reacted sample was vacuum filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH≈7). Finally, the obtained sample was freeze-dried to obtain the surface-functionalized MXene. 3 M alkali-treated surface-modified MXene was then dissolved in 1 M Al(NO3)3 solution with 1 Ag... -1 The specific capacitance at current density is 174 Fg -1 .
[0044] Example 7 Steps 1-3 are the same as in Example 1.
[0045] 150 mg of few-layer Ti3C2T x Dispersed in 100 mL of 3 M phenanthrene solution (added while stirring), the sample was continuously purged with argon gas for 30 minutes. The glass bottle was sealed, and the mixture was stirred at 900 rpm for 24 h at room temperature to obtain the intercalated sample, 3M alkali-treated surface-modified MXene. The reacted sample was vacuum filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH≈7). Finally, the obtained sample was freeze-dried to obtain the surface-functionalized MXene. 3M alkali-treated surface-modified MXene was dissolved in 1 M Al(NO3)3 solution with 1 Ag... -1 The specific capacitance at current density is 115 Fg -1 .
[0046] Example 8 Steps 1-3 are the same as in Example 1.
[0047] 150 mg of few-layer Ti3C2T x Dispersed in 100 mL of 5 M bipyridine solution (added while stirring), the sample was continuously purged with an inert protective gas, argon, for 30 minutes. The glass bottle was sealed, and the mixture was stirred at 900 rpm for 24 h at room temperature to obtain the intercalated sample, 5 M alkali-treated surface-modified MXene. The reacted sample was vacuum filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH≈7). Finally, the obtained sample was freeze-dried to obtain the surface-functionalized MXene. 5 M alkali-treated surface-modified MXene was then dissolved in 1 M Al(NO3)3 solution with 1 Ag...-1 The specific capacitance at current density is 121 F.g -1 .
[0048] This invention proposes a simple alkali-assisted intercalation strategy for synthesizing atomic-scale MXene-N nanosheets with a surface rich in (-N). By precisely controlling the alkali concentration, the interlayer spacing and surface electron cloud density of MXene are adjusted, significantly improving its electrochemical performance in various nitrate electrolytes. 2,2'-Bipyridine intercalation effectively expands the interlayer spacing of MXene, making its layered structure more porous and exhibiting a sheet-like morphology, thereby increasing the contact area between MXene and the electrolyte and providing more reactive sites. Furthermore, during alkali treatment, the increased electron cloud density of Ti enhances the surface negative charge density, facilitating ion adsorption through electrostatic attraction. Further adjustment of the alkali concentration can optimize the electrochemical performance and stability of the electrode. This interlayer space adjustment strategy provides new ideas and possibilities for the application of MXene in energy storage.
[0049] The above embodiments are merely preferred technical solutions of the present invention and should not be considered as limitations on the present invention. The embodiments and features described in these embodiments can be arbitrarily combined without conflict. The scope of protection of the present invention should be limited to the technical solutions described in the claims, including equivalent substitutions of the technical features described in the claims. That is, equivalent substitutions and improvements within this scope are also within the scope of protection of the present invention.
Claims
1. A method for preparing alkali-treated surface-modified MXene material, characterized in that, The synthesis method includes the following steps: (1) Ti3AlC2 powder was slowly added to polytetrafluoroethylene containing concentrated HCl and LiF to etch the aluminum layer. After etching, the mixture was washed until neutral. (2) The product obtained in step (1) is dispersed in water and degassed by continuously passing inert gas. After being sealed and ultrasonically peeled at room temperature, the resulting dispersion is centrifuged and the supernatant is freeze-dried to obtain a few-layer Ti3C2T x Nanosheets; (3) Weigh out a small layer of Ti3C2T x Nanosheets were slowly added to an alkaline solution under stirring, and the reaction was carried out under an inert gas atmosphere. The reacted sample was then vacuum filtered, and the filter cake was washed with water until the filtrate was neutral. Finally, the sample was freeze-dried to obtain surface-functionalized MXene.
2. The method for preparing alkali-treated surface-modified MXene material according to claim 1, characterized in that, Step (1) The mass ratio of Ti3AlC2 to LiF is 1:1-2; the mass concentration of concentrated HCl is 36-38%.
3. The method for preparing alkali-treated surface-modified MXene material according to claim 1, characterized in that, The etching temperature of the aluminum layer in step (1) is 40-70℃ and the etching time is 24-72 h.
4. The method for preparing alkali-treated surface-modified MXene material according to claim 1, characterized in that, The Ti3C2T mentioned in step (2) x The concentration of the dispersion is 8-12 mg / mL. -1 .
5. The method for preparing alkali-treated surface-modified MXene material according to claim 1, characterized in that, The inert atmosphere in step (2) is selected from either nitrogen or argon, the ultrasonic stripping time is 8-15 h, and the centrifugation speed is 3000-5000 rpm. -1 .
6. The method for preparing alkali-treated surface-modified MXene material according to claim 1, characterized in that, The base mentioned in step (3) is selected from any one or more combinations of 2,2'-bipyridine, 2,3'-bipyridine, 2,4'-bipyridine, 4,4'-bipyridine, acridine or phenanthridine.
7. The method for preparing alkali-treated surface-modified MXene material according to claim 6, characterized in that, The concentration of the alkali is 1-5 M, and the Ti3C2T... x The dispersion concentration in alkaline solutions is 0.5-2 mg / mL. -1 .
8. The method for preparing alkali-treated surface-modified MXene material according to claim 1, characterized in that, After adding the alkaline solution in step (3), the reaction is carried out under the inert gases of argon and nitrogen, with the stirring speed controlled at 800-900 rpm for 20-30 h.
9. The method for preparing alkali-treated surface-modified MXene material according to claim 1, characterized in that, The freeze-drying time in step (2) is 5-7 days.
10. The application of the modified MXene material obtained by the method according to any one of claims 1-9 in an electrochemically active electrode.